2018–2019 Florida Citrus Production Guide: Best Management Practices for Soil-Applied Agricultural Chemicals - Joseph W. Noling; Lawrence R. Parsons (EDIS)
This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. The purpose of this document is to provide information that can help citrus growers and caretakers select and manage agricultural chemicals in ways which will minimize environmental impact. These BMPs must consider the soil properties of the application site and the mobility and toxicity of agrichemicals in soil, particularly with regard to rainfall and irrigation practices. With these considerations in mind, citrus growers can hopefully make better, more informed decisions regarding the chemicals that they use. Written by J. W. Noling and L. R. Parsons, and published by the Horticultural Sciences Department, January 2019.